Institutionality and projects in the Church: Towards a theoretical understanding of the practice of the Church - Cortázar Velarde, Juan Carlos (1988)
Little attention has been paid by Peruvian Social Sciences to the study of the Catholic Church. Although there is a wide body of works on religious phenomena in general, very few of them refer to the largest religious institution in the country. The few studies that take up this subject generally lack a deep and adequate theoretical framework, perhaps due in part to this lack of interest.